2014
DOI: 10.1016/j.fob.2014.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Identification of nuclear phosphoproteins as novel tobacco markers in mouse lung tissue following short‐term exposure to tobacco smoke

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 65 publications
2
6
0
Order By: Relevance
“…It has been reported that the transcription factor (TF) STAT can be activated after tobacco smoke exposure. 46 Functional prediction analysis from HaploReg showed that rs3769201 had a STAT binding site motif, and the results of eQTL in the present study also demonstrated that the SNP may alter the mRNA expression of ZAK. However, there is no significant difference between ever smokers and never smokers as tested by the heterogeneity test.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…It has been reported that the transcription factor (TF) STAT can be activated after tobacco smoke exposure. 46 Functional prediction analysis from HaploReg showed that rs3769201 had a STAT binding site motif, and the results of eQTL in the present study also demonstrated that the SNP may alter the mRNA expression of ZAK. However, there is no significant difference between ever smokers and never smokers as tested by the heterogeneity test.…”
Section: Discussionsupporting
confidence: 72%
“…Cigarette smoke is the major risk factor for lung cancer, especially for SC. It has been reported that the transcription factor (TF) STAT can be activated after tobacco smoke exposure . Functional prediction analysis from HaploReg showed that rs3769201 had a STAT binding site motif, and the results of eQTL in the present study also demonstrated that the SNP may alter the mRNA expression of ZAK .…”
Section: Discussionsupporting
confidence: 64%
“…The 2D-DIGE method is a useful tool to reveal functional post-translational modifications of nuclear factors that cannot be detected with DNA microarray. A shotgun proteome approach using nano-liquid chromatography (nanoLC) tandem mass spectrometry incorporating phosphopeptide enrichment can detect phosphorylated peptides in a highly sensitive manner 32 . However, proteomics analysis using 2D-DIGE can clearly indicate the molecular weight and pH of proteins in 2D-electrophoresis, provides more credible results concerning nuclear protein identification, and displays better quantitative reproducibility.…”
Section: Discussionmentioning
confidence: 99%
“…Nicotine can induce cell proliferation, invasion, and metastasis in several cancers [27, 28]. Nicotine-induced Prx1 overexpression correlates significantly with OSCC carcinogenesis [12, 29], and further investigation of the functional role of Prx1 could provide a novel biomarker for OSCC prevention and therapy.…”
Section: Discussionmentioning
confidence: 99%